2013
DOI: 10.1073/pnas.1314145110
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Sirtuin ratio reversed by ApoE4

Abstract: The canonical pathogenesis of Alzheimer's disease links the expression of apolipoprotein E e4 allele (ApoE) to amyloid precursor protein (APP) processing and Aβ peptide accumulation by a set of mechanisms that is incompletely defined. The development of a simple system that focuses not on a single variable but on multiple factors and pathways would be valuable both for dissecting the underlying mechanisms and for identifying candidate therapeutics. Here we show that, although both ApoE3 and ApoE4 associate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 29 publications
4
75
1
3
Order By: Relevance
“…As SirT1 has previously been shown to activate transcription of ADAM10 [52] and thus increase levels of neuroprotective sAPPα [53,54], one can conclude that a decrease in SirT1 expression as a result of the presence of ApoEε4 is likely to lead to decreased sAPPα levels. In further support of a role for ApoEε4 effects on SirT1 expression and ultimately sAPPα production, we showed that increasing SirT1 expression in the presence of ApoEε4 restores sAPPα levels in vitro by co-transfecting A172 cells with both ApoEε4 and SirT1 and identifying increases in sAPPα of 10% (1:1) or 20% (1:2) as compared to ApoEε4 transfection alone [47].As a result of these findings, we added SirT1 enhancement as a target for our in vitro screens to identify new small molecules for potential development as AD therapeutics. This resulted in our identification of brain-permeable small molecules that increase SirT1, sAPPα, and cell survival in vitro (manuscript in preparation).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…As SirT1 has previously been shown to activate transcription of ADAM10 [52] and thus increase levels of neuroprotective sAPPα [53,54], one can conclude that a decrease in SirT1 expression as a result of the presence of ApoEε4 is likely to lead to decreased sAPPα levels. In further support of a role for ApoEε4 effects on SirT1 expression and ultimately sAPPα production, we showed that increasing SirT1 expression in the presence of ApoEε4 restores sAPPα levels in vitro by co-transfecting A172 cells with both ApoEε4 and SirT1 and identifying increases in sAPPα of 10% (1:1) or 20% (1:2) as compared to ApoEε4 transfection alone [47].As a result of these findings, we added SirT1 enhancement as a target for our in vitro screens to identify new small molecules for potential development as AD therapeutics. This resulted in our identification of brain-permeable small molecules that increase SirT1, sAPPα, and cell survival in vitro (manuscript in preparation).…”
supporting
confidence: 63%
“…Our recent studies have connected ApoEε4 expression with the major longevity determinants, sirtuins [47]. We showed that ApoEε4 -but not ApoEε3 -associates with APP with nanomolar affinity (Kd ~80 nM), and that only ApoEε4 significantly reduces the sAPPα/Aβ ratio.…”
Section: Apoeε4 Sirt1 and Sappα In Admentioning
confidence: 92%
“…Co-transfection of huAPPwt and ApoE ε4 has been shown to significantly decrease sAPPα secretion, and reduce the sAPPα/sAPP β or sAPPα/A β –1-40 ratio in several cell lines, and tropisetron – identified as “F03” - has been shown to reverse these reductions (Theendakara, 2013). Here we also show that tropisetron at 1μM significantly increased cell survival of both ApoE ε3- and ApoE ε4-transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous physiological parameters that feed into this balance, such as hormones [28, 29], trophic factors [18], glucose metabolism [30], inflammatory mediators [31], ApoE genetic status [32] sleep-related factors [33], exercise-related factors [34], and many others; therefore, the therapeutic system is designed to reverse the self-reinforcing (i.e., prionic) signaling imbalance that we have hypothesized to mediate Alzheimer's disease pathophysiology [8]. …”
Section: Discussionmentioning
confidence: 99%